2016
DOI: 10.1093/jnci/djw100
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 Sublineage Associations With Histology-Specific Cancer Risk Using HPV Whole-Genome Sequences in 3200 Women

Abstract: Specific HPV16 variant sublineages strongly influence risk of histologic types of precancer and cancer, and viral genetic variation may help explain its unique carcinogenic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
231
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(253 citation statements)
references
References 46 publications
16
231
4
2
Order By: Relevance
“…Differences in the oncogenic potential displayed by variants of the same HPV type have been described; HPV16 B, C, D2 and D3 variants promote a 3-fold higher risk of cervical cancer development compared to the A1 sublineage. The non-European HPV18 variants are identified more frequently in cancer tissues and high-grade squamous lesions [31,34,35,36]. HPV33 (C7732G) and HPV58 (C632T and G760A) variants have been associated with a higher risk of cervical cancer development [37,38].…”
Section: Hpv Diversity and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the oncogenic potential displayed by variants of the same HPV type have been described; HPV16 B, C, D2 and D3 variants promote a 3-fold higher risk of cervical cancer development compared to the A1 sublineage. The non-European HPV18 variants are identified more frequently in cancer tissues and high-grade squamous lesions [31,34,35,36]. HPV33 (C7732G) and HPV58 (C632T and G760A) variants have been associated with a higher risk of cervical cancer development [37,38].…”
Section: Hpv Diversity and Cancermentioning
confidence: 99%
“…HPV33 (C7732G) and HPV58 (C632T and G760A) variants have been associated with a higher risk of cervical cancer development [37,38]. In addition, the HPV16 D2 and D3 sublineages are associated with adenocarcinoma [36,39]. Some studies suggest that a higher risk for cervical cancer development is not only related to the HPV variant/sublineage, but also dependent on ethnicity.…”
Section: Hpv Diversity and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, persistent infections with certain variants of HPV16, the genotype found in approximately half of all cervical cancers [4], differ in cancer risk. These variants diverge in their biological properties; therefore, they may become important risk factors in cervical cancer because of possible differences in pathogenicity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sublineage A1 can be divided into isolates containing either 350T (EUR-350T, which includes the prototype HPV16 sequence) or 350G (EUR-350G). Epidemiological studies have suggested that this polymorphism might promote persistent viral infection and cervical cancer development [8,9,14,15]: HPV16 variants with mutations in E6 have been reported for cervical High-grade Squamous Intraepithelial Lesions (HSIL), invasive cervical cancer, and anal HSIL [16][17][18][19][20]. More precisely, in epidemiological study of the French population, a specific intratype polymorphism, such as the EUR-350G isolate, has been found to induce a greater risk of persistence and progression than the E6 prototype [8].…”
Section: Introductionmentioning
confidence: 99%